2016
DOI: 10.1016/j.scitotenv.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

A review of the environmental implications of in situ remediation by nanoscale zero valent iron (nZVI): Behavior, transport and impacts on microbial communities

Abstract: The increasing use of strategies incorporating nanoscale zero valent iron (nZVI) for soil and groundwater in situ remediation is raising some concerns regarding the potential adverse effects nZVI could have on indigenous microbial communities and ecosystem functioning. This review provides an overview of the current literature pertaining to the impacts of nZVI applications on microbial communities. Toxicity studies suggest that cell membrane disruption and oxidative stress through the generation of Fe2+ and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
121
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 334 publications
(129 citation statements)
references
References 99 publications
(175 reference statements)
4
121
0
4
Order By: Relevance
“…In contrast, the peaks for Cd 3d 5/2 in the XPS data collected on day 30 from new cultures and those collected on days 2 and 10 from 11-day old cultures were found at 404.8 eV ( Figure 3, Table S3) and assigned to Cd(OH) 2 . We previously showed that the pH of COMBO media (which contains no buffer) increases over time when C. reinhardtii cells are cultured in it.…”
Section: Resultsmentioning
confidence: 91%
“…In contrast, the peaks for Cd 3d 5/2 in the XPS data collected on day 30 from new cultures and those collected on days 2 and 10 from 11-day old cultures were found at 404.8 eV ( Figure 3, Table S3) and assigned to Cd(OH) 2 . We previously showed that the pH of COMBO media (which contains no buffer) increases over time when C. reinhardtii cells are cultured in it.…”
Section: Resultsmentioning
confidence: 91%
“…The Fe 0 in water was oxidized by O 2 , producing Fe 2+ , which can be subsequently oxidized to Fe 3+ and generate iron oxides. Therefore, much of the O 2 was consumed as result of iron corrosion, according to Eqns (1–3): Fe0+H2normalO+1false/20.25emO2Fe2++2OH Fe2++1false/20.25emH2normalO+1false/40.25emO2Fe3++OH Fe3++3H2normalOnormalFenormalOH3+3H+ …”
Section: Resultsmentioning
confidence: 99%
“…The Sb(V) removal rate by mZVI was reduced by 6.6–16%. This was likely due to the absence of soluble Fe 2+ , which is normally produced by the anaerobic corrosion of Fe 0 , according to Eqn : Fe0+2H2normalOFe2++H2+2OH …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, field and laboratory bench‐scale observations indicate that nZVI use is synergistic and stimulatory for in situ anaerobic biodegradation of chlorinated solvents by dehalorespiration. While nZVI has been shown to be inhibitory to micro‐organisms (Lefevre, Bossa, Wiesner, & Gunsch, ), laboratory studies have also found that nZVI application does not appear to be inhibitory to (and may even be stimulatory for) biological reductive dechlorination associated with water‐derived cathodic H 2 production during its anaerobic corrosion (Comba, Di Molfetta, & Sethi, ; Kirschling, Gregory, Minkley, Lowry, & Tilton, ; Xiu et al., ). Kuang, Zhou, Chen, Megharaj, and Naidu () found corroborating results supporting this theory, demonstrating that both nZVI and Ni/Fe composite NPs increased the biodegradation of phenol by Bacillus fusiformis at pH 6 and 8; nZVI was also demonstrated to increase biodegradation at low pH (pH 3).…”
Section: Risk‐benefit Appraisal For Nanorem Technologiesmentioning
confidence: 99%
“…NPs are able to migrate farther in soil and groundwater compared with micro‐scale ZVI, which is essentially immobile (Lefèvre, ; Müller, ).…”
Section: Benchmarking and Technologies Cross‐comparisonsmentioning
confidence: 99%